Redefining Woman's Worth: The Ambiguous Nature of Female Identity in Two Novels by Margaret Laurence - Styles, Christine (My University, 1999)
The impulse to attain "wholeness", to create and sustain a coherent identity, is a central issue in Margaret Laurence's novels A Jest of God (1966) and The FireDwellers (1969). This thesis will examine the immobilization and discontent that arise when women are unable to mediate between their personal desires and the social values that are imposed upon them. The two novels are unified by Laurence's contention that women must become agents of change rather than maintain a passive or responsive stance in their social roles. In keeping with her belief in the value of diversity, Laurence's novels "reject those aspects of female identity which society imposes on women, including conventional 'femininity', heterosexuality, wifehood, and motherhood" (Relke 37). This is not to suggest that Laurence advocates the abandonment of traditional roles. Rather, she focuses upon the paradox of identity formation in which the subject must both reject and rely upon institutionalized norms and mores. Only when women acknowledge the ambiguity that they feel towards their socially constructed roles will they be able to recognize and confront the power structures that impinge on their lives and restrict their emotional and intellectual expression.
Keywords: English Language and Literature; English Language and Literature